2019
DOI: 10.1111/jav.01823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tracking devices on individual birds – a review of the evidence

Abstract: We review long‐term patterns of tracking device use and the reporting of the effects of such devices on individual birds. We assessed > 3400 primary references including > 1500 containing information as to whether effects were looked for and reported. Numbers of papers published increased at 4.4% yr–1. Research on foraging and energetics focussed on seabirds while work on habitat use and dispersal was focussed mainly on landbirds. Migration was the most common study topic overall and increased markedly from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 42 publications
7
107
0
Order By: Relevance
“…For vertebrates, protocols regarding ethical research methodologies are well adopted and monitored by ethics committees (Drinkwater et al, 2019;Kays et al, 2015). Guidelines for the use and impact assessment of tracking devices for vertebrates are actively being developed and refined (Barron et al, 2010;Geen et al, 2019;McIntyre, 2015;Portugal & White, 2018). While the development of devices for tracking arthropods has sprung from technological knowledge gained from vertebrate research, ethical concerns and guidelines about impact assessment were not co-adopted.…”
Section: Con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…For vertebrates, protocols regarding ethical research methodologies are well adopted and monitored by ethics committees (Drinkwater et al, 2019;Kays et al, 2015). Guidelines for the use and impact assessment of tracking devices for vertebrates are actively being developed and refined (Barron et al, 2010;Geen et al, 2019;McIntyre, 2015;Portugal & White, 2018). While the development of devices for tracking arthropods has sprung from technological knowledge gained from vertebrate research, ethical concerns and guidelines about impact assessment were not co-adopted.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Furthermore, while the '5% rule', that is, the device mass should be no more than 5% of the animal mass, is often used as a guideline for swimming and flying vertebrates (Aldridge & Brigham, 1988;Kenward, 2000), it has a weak empirical basis and is often disregarded (Barron et al, 2010;O'Mara, Wikelski, & Dechmann, 2014;Portugal & White, 2018). These ethical and scientific drawbacks have resulted in recent guidelines and recommendations regarding the use of tracking devices on birds and mammals (Casper, 2009;Kays et al, 2015;Mcintyre, 2014;O'Mara et al, 2014;Wilson & McMahon, 2006) and a call for more systematic documentation of potential effects (Geen, Robinson, & Baillie, 2019).…”
mentioning
confidence: 99%
“…The use of tracking devices has substantially advanced our understanding of animal ecology and behaviour (Kays et al 2015), allowing unprecedented insight into individual behaviour, movement and population processes (McKinnon and Love 2018). However, tracking devices can negatively affect an individual's reproduction, survival and movements, and have rightly been subject to extensive review (Calvo and Furness 1992;Murray and Fuller 2000;Barron et al 2010;Costantini and Møller 2013;Bodey et al 2018;Geen et al 2019). Such effects vary with study species, transmitter types (GPS/ GSM, GPS-loggers, Argos/GPS PTTs, accelerometers, geolocators), attachment method (glue adhesion, tail-mount, leg-ring, necklace, leg-loop, harnesses) and mass of device relative to the animal (see reviews above).…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners deploying transmitters clearly want to minimise transmitter effects and often base their methodologies on guidelines, such as the 3% or 5% transmitter relative to body weight 'rule', or use a system that was deemed successful for a similar species. However, recent meta-analyses confirmed that there was no device mass threshold below which effects were not observed (Bodey et al 2018;Geen et al 2019). Furthermore, when extrapolating results of one tagging study to another, similar physiognomies of the target species may not always be enough to predict transmitter effects (Thaxter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation